Measuring the Mutual Fund Industry Risk Management and Performance Sustainability - Quantile Regression Model - Lee, Joe-Ming (Journal of Asian Business Strategy, 2013)
We apply the Quantile Regression Model to observe the rank correlation between bond fund performance and asset, volatility, management fee, Sharpe index and show that fund performance between volatility as a negative significant relationship, implied extreme values have been generated risk coefficient and fund performance change relations. The extreme value of the display the risk coefficient fund performance has changed the relationship, show that enhance the risk coefficient, resulting in lower fund performance, tells us that the mutual fund industry pursuit of short-term fund performance through operating the transition risks lever, but cannot afford a long-term test of the market. Finally, we recommend that the mutual fund industry needs to strengthen risk management professional and pursuit of performance Sustainability.